POTENSI GETAH PINUS DI KHDTK HUTAN PENDIDIKAN UNIVERSITAS HASANUDDIN - Hidayat, Fathul; Dassir, Muhammad; Vika, Vika (Jurnal Riset Multidisiplin Agrisosco, 2023)
Pine sap is the result of tapping pine trees. Of course, tapping pine sap requires quite a lot of labor. Indirectly, this can be used as a source of income for the community around the forest area. Hasanuddin University Education Forest has a potential pine area of 64.64 Ha which is in the utilization block. The data collection technique carried out in this study is the literature study technique. There are 119 trees / ha located in location 1 and have sap potential of 22054.67 g / ha / day and in locations 2 and 3 each have 90 and 113 trees and have sap potential of 16680 and 20942.67 g / ha / day with an average yield of 19892.44 g / ha / day.